Determinan Minat Ibu dalam Pemilihan Kontrasepsi IUD di Wilayah Kerja Puskesmas Mandrehe Utara Kabupaten Nias Barat - Nuryudica Harefa; Efentinus Ndruru (Journal of Issues in Midwifery, 2022)
Background: IUDs are an effective, safe and comfortable contraception option for many women. IUD contraceptive users in North Mandrehe Health Center were 12 active acceptors and 3 new acceptors. The purpose of this study was to determine the affecting factors on the low interest of mothers in choosing an IUD as a contraceptive. Method: This study uses an analytical survey with a cross sectional approach. This research was conducted at North Mandrehe Health Center. The sample of this study was fertile age couple who used contraception as many as 98 respondents. The data were analyzed by performing Chi-square analysis and multiple linear analysis. Result: Based on the results of the study obtained variables of age, education, occupation, economy, knowledge, husband's support, socio-cultural, and health worker support have a relationship to the mother's interest in choosing an IUD as a contraceptive, while the variable that has no relationship was the parity variable. One of the main factors that most influence was the knowledge variable (OR = 8,766). Conclusion: The conclusion of this study showed that there were factors (age, education, occupation, economy, knowledge, husband's support, socio-cultural, and health worker support) that influence the mother's interest in choosing an IUD. It was suggested to health workers at North Mandrehe Health Center to intensely conduct counseling to the community, especially about IUD contraceptives.